2018
DOI: 10.1084/jem.20171440
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation of tumor-associated macrophages boosts preexisting tumor immunity

Abstract: Combined CSF-1R+CD40 antibody therapy induces profound and rapid TAM reprogramming before TAMs are eliminated. This combination of cancer immunotherapies tailored to activate the innate immune system creates an inflamed tumor microenvironment ultimately leading to tumor eradication by the adaptive immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 71 publications
8
136
1
Order By: Relevance
“…Other very recent studies have demonstrated interesting strategies for the in vivo modulation of TAMs. In a murine colon adenocarcinoma model, treatment with two mAbs to concomitantly block CSF‐1R and stimulate CD40 resulted in the reprogramming of TAMs by increasing pro‐inflammatory signals such as IL‐12B, IL‐27, IL‐1β and CCL5 . In addition, in a melanoma tumor model, the depletion of CD163 + TAMs, using an anti‐CD163 antibody conjugated to a doxorubicin charged liposome, led to a monocyte influx, the up‐regulation of IFN‐related cytokines and an anti‐tumor T‐cell response …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other very recent studies have demonstrated interesting strategies for the in vivo modulation of TAMs. In a murine colon adenocarcinoma model, treatment with two mAbs to concomitantly block CSF‐1R and stimulate CD40 resulted in the reprogramming of TAMs by increasing pro‐inflammatory signals such as IL‐12B, IL‐27, IL‐1β and CCL5 . In addition, in a melanoma tumor model, the depletion of CD163 + TAMs, using an anti‐CD163 antibody conjugated to a doxorubicin charged liposome, led to a monocyte influx, the up‐regulation of IFN‐related cytokines and an anti‐tumor T‐cell response …”
Section: Discussionmentioning
confidence: 99%
“…In a murine colon adenocarcinoma model, treatment with two mAbs to concomitantly block CSF-1R and stimulate CD40 resulted in the reprogramming of TAMs by increasing pro-inflammatory signals such as IL-12B, IL-27, IL-1b and CCL5. 44 In addition, in a melanoma tumor model, the depletion of CD163 + TAMs, using an anti-CD163 antibody conjugated to a doxorubicin charged liposome, led to a monocyte influx, the up-regulation of IFN-related cytokines and an anti-tumor T-cell response. 45 Importantly, we described for the first time that conditioned-media supernatants of dilacerated primary human breast tumors promote either highly suppressive CD163 high IL-10 high CD86 low MΦ, resembling suppressive TAMs, [46][47][48] or CD163 low IL-10 low CD86 low MΦ, displaying moderate suppressive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Repolarized TAMs could therefore become efficient antigen-presenting cells activating CD8 and CD4 T cells in situ (21). TAM repolarization strategies include agonistic anti-CD40 (aCD40), blockade of CSF1 signaling, selective inhibition of PI3Kg, deletion of Dicer, as well as targeting surface markers expressed by suppressive macrophages (2,8,16,(21)(22)(23)(24)(25)(26)(27)(28). Repolarization and depletion have recently been combined to achieve an optimal stimulatory phenotype on macrophages; however, its implication on tumor sensitization to checkpoint inhibitors remains unclear (27).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the ability of JHU083 to inhibit growth of EO771, which is similar to 4T1 triple negative breast cancer. The EO771 tumor model is moderately sensitive to immunotherapy in the form of anti-PD1 monotherapy or anti-CSF1R + anti-CD40 combination immunotherapy (Hoves et al, 2018). We observed significant inhibition of tumor growth and enhanced survival with JHU083 treatment alone (Supplementary figure 6A and B).…”
Section: The Glutamine Antagonist Jhu083 Enhances the Efficacy Of Chementioning
confidence: 71%
“…Recently, multiple studies have demonstrated that pro-inflammatory TAMs inhibit tumor growth (Hoves et al, 2018;Perry et al, 2018). Our RNA sequencing data of TAMs from JHU083 treated mice demonstrated an increase in the pro-inflammatory cytokine, Tnf.…”
Section: Targeting Glutamine Metabolism Promotes the Reprogramming Ofmentioning
confidence: 72%